The Phonetic Analysis of Trademarks - Castañeda Peñaloza, Claudio (2017)
In this paper we will present parameters for the comparative analysis of trademarks in their phonetic dimension. In the first part, as conceptual framework, general notions of phonology and phonetics are introduced, which are later applied in a critical jurisprudential analysis of relevant decisions from Argentina, Chile, Colombia and Peru. To complement the scope of this investigation, in the third part we discuss the need to unify criteria of appreciation of trademarks with foreign phonetics. Thus, this work aims to provide tools for the argumentation and grounding of trademarks phonetic comparison and, along with it, emphasizes the need to adopt an unique model of trademark comparison based on the science of signs: semiotics or semiology. A methodology in this sense would strengthen the reasoning of litigants, administrative and judicial authorities regarding the risk of confusion, avoiding that the comparison of trademarks falls into mere subjectivity.